Ministry Of Finance Decree No. 269 of the Year 2018 on the Collection of the Government, Tax and Customs Dues via the Electronic Payment and Collection System = وزارة المالية قرار رقم 269 لسنة 2018 بشأن تحصيل المستحقات الحكومية والضريبية والجمركية من خلال منظومة الدفع والتحصيل الإلكترونى - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic